The growth-employment-poverty nexus in Latin America in the 2000s: Paraguay country study - Guillermo Cruces; Gary Fields; David Jaume; Mariana Viollaz (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
During the 2000s Paraguay experienced slow economic growth but improved all labour market indicators. The growth process was erratic. Paraguay underwent a macroeconomic crisis at the beginning of the period, a recession as a consequence of the international crisis of 2008, and a local crisis in 2012. Most labour market indicators improved between 2001 and 2013 following the erratic pattern of GDP. The only labour market indicator that improved almost steadily over the period was the educational level of the employed population. All poverty and inequality indicators exhibited an erratic behaviour over time, but fell overall between 2001 and 2013.
Keywords: O15; J01; J30; 330; Paraguay; Latin America; inclusive growth; labour market; poverty